Environmental factors and oncology and cardiology : lecture notes on air, water and soil, life style, human ecology and sustainable development - Hens, Luc (Charles University, 1996)
Lecture notes that focus on the impact of environmental pollution on the development of cardiovascular diseases and cancer. Intended for the professional public.
Lectures on the Environment for oncologists and cardiologists
Keywords: kardiovaskulární nemoci; Cardiovascular Diseases; onkologie; znečištění životního prostředí; látky znečišťující životní prostředí; Environmental Pollutants; nemoc vyvolaná prostředím; nádory; kardiologie; environmentální vědy; Environmental Pollution; Environmental Illness; Neoplasms